COMPOSITIONAL STUDY ON ORE FLUID OF THE YINDONGGOU SILVER DEPOSIT IN NEIXIANG COUNTY, HENAN PROVINCE, CHINA - Zhang J.; You S.N.; Qi J.P.; Qiu J.J.; Li G.P. (My University, 2007)
The Yindonggou silver deposit is a fault-controlled lode deposit, occurring in the Erlangping Terrane, the northeastern Qinling Orogen. It is hosted in the sericite-quartz schist of the Xiaozhai Formation, Erlangping Group. In this paper the deposit is determined to be of orogenic-type in terms of a systematic study of the molecular, ion and rare earth elements compositions of fluid inclusions. With CO2-content ranging 12.829% ∼ 22. 172mol%, the fluid inclusions are dominated by CO2-NaCl-H2O composition, which characterizes the orogenic-type fluid-systems worldwide. The ore-fluids were mainly derived from metamorphic devolatilization of marine carbonate-containing lithologies in early stage, and boiled in middle stage and evolved into a meteoric water-dominated fluid-system in late stage. The ore metals, such as Ag, through coordinating with Cl- and other anions anions, were extracted and enriched into fluids and then transported in early stage. Fluid-boiling probably caused rapid precipitation of ore metals in middle stage. Differences in contents of REE, Mg2+, Ca2+ and other ions in fluid inclusions between different levels and/or metallogenic stages can be related to hydrothermal alterations of wall-rocks.
Keywords: HENAN PROVINCE; ORE-FLUID; OROGENIC-TYPE DEPOSIT; QINLING OROGEN; YINDONGGOU SILVER DEPOSIT